Studi terhadap Hadis yang Sering Disalahgunakan untuk Mendukung Aksi Terorisme - Siregar, Idris; Hasyim, Uday; Rabbani, M. Yaffi (TSAQOFAH, 2024)
Terrorism is an extreme activity that can take the lives of many people and is very detrimental to various parties. This study aims to conduct a critical analysis of hadiths that are often abused by terrorist groups to support acts of violence and terrorism. The research method used is a literature review with a content analysis approach to hadith texts as well as the interpretation of classical and contemporary scholars. This study found that the hadiths that are often used as justifications by terrorist groups actually have a different historical context and meaning than what is understood by the perpetrators of terrorism. By understanding the context and proper interpretation, these hadiths should teach peace, tolerance, and justice. The study also highlights the important role of Muslim scholars and scholars in providing a correct understanding of Islamic teachings to prevent the misuse of hadith in acts of violence. The findings of this research are expected to contribute to efforts to deradicalize and counter terrorism, as well as strengthen the understanding of Islam which is rahmatan lil 'alamin.